Spatially modulated illumination microscopy: application perspectives in nuclear nanostructure analysis - Cremer, Christoph; Birk, Udo J. (Philosophical transactions of the Royal Society. A, Mathematical, physical and engineering sciences, 2022)
Thousands of genes and the complex biochemical networks for their transcription are packed in the micrometer sized cell nucleus. To control biochemical processes, spatial organization plays a key role. Hence the structure of the cell nucleus of higher organisms has emerged as a main topic of advanced light microscopy. So far, a variety of methods have been applied for this, including confocal laser scanning fluorescence microscopy, 4Pi-, STED- and localization microscopy approaches, as well as (laterally) structured illumination microscopy (SIM). Here, we summarize the state of the art and discuss application perspectives for nuclear nanostructure analysis of spatially modulated illumination (SMI). SMI is a widefield-based approach to using axially structured illumination patterns to determine the axial extension (size) of small, optically isolated fluorescent objects between less than or equal to 200 nm and greater than or equal to 40 nm diameter with a precision down to the few nm range; in addition, it allows the axial positioning of such structures down to the 1 nm scale. Combined with SIM, a three-dimensional localization precision of less than or equal to 1 nm is expected to become feasible using fluorescence yields typical for single molecule localization microscopy applications. Together with its nanosizing capability, this may eventually be used to analyse macromolecular complexes and other nanostructures with a topological resolution, further narrowing the gap to Cryoelectron microscopy. - - This article is part of the Theo Murphy meeting issue ‘Super-resolution structured illumination microscopy (part 2)’.